Endothelial Cell Density before and after Phacoemulsification in patients with Diabetes Mellitus - Shahbaz Aslam, Maha Saher, Muhammad Rashad Qamar Rao, MM Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Cataract is the leading cause of treatable blindness worldwide. Phacoemulsification with intraocular lens (IOL) implantation is the most common surgical procedure performed for the treatment of cataract. The diabetic cornea has decreased corneal endothelial cell density (CED) due to cell dysfunction and malfunctioning repair systems. Objective: To compare the mean endothelial cell density before and after phacoemulsification in patients with diabetes mellitus. Material and Methods: A total number of 30 patients who presented for cataract extraction were included. Data regarding patients age, gender, duration of diabetes mellitus and side of cataract was collected. One day before surgery, CED was measured in all patients using Specular Microscope. After 2 weeks of surgery, CED was measured again. Results: Mean age of patients included in this study was 48.70±8.39 years. Mean duration of diabetes mellitus was 5.03±2.85 years. There were 16 (53.33%) males and 14 (46.67%) female patients. There were 15 (50.00%) patients with right eye and also 15 (50.00%) with left eye. On comparison of mean ECD between the Groups, the mean pre-operative ECD was 2753.05±126.91 Cells/mm2 and post-operative ECD was 2451.16±160.93 Cells/mm2, this difference was statistically significant with p value <0.0001. Conclusion: Phacoemulsification is associated with significant decrease in endothelial cell density in diabetic patients presenting with cataract. The benefit of this study is that it adds to the existing body of literature on impact of phacoemulsification on endothelial cell density in diabetic patients which can help in the development of advanced surgical techniques and better post operative management in such patients. Keywords: Endothelial cell density, phacoemulsification, diabetes mellitus.